A new species and first record of the cicada genus Sinotympana Lee, 2009 (Hemiptera: Cicadidae: Dundubiini) from Vietnam - Pham, Thai-Hong; Sanborn, Allen F.; Nguyen, Huyen-Thi; Constant, Jerome (Zootaxa, 2019)
The first record of the genus Sinotympana Lee, 2009 from Vietnam is presented. Sinotympana caobangensis sp. nov. (Hemiptera: Cicadidae) from Phia Oac—Phia Den National Park, Cao Bang Province, northern Vietnam is described as new. Photographs of an adult male, illustrations of the male genitalia, a distribution map and biological data for Sinotympana caobangensis sp. nov. are provided.